Features of Labour Productivity Measurement in Medical Organizations of the Kemerovo Region – Kuzbass - Artem N. Popsuyko; Galina V. Artamonova (Вестник Кемеровского государственного университета. Серия: политические, социологические и экономические науки)
The article is devoted to the problem of measuring labor productivity in healthcare. In the absence of a generally accepted standard for evaluating this indicator, the study uses a quantitative approach based on the analysis of the visits and doctors numbers dynamics in medical organizations of the Kemerovo Region. The purpose of the study is to analyze the dynamics and make a forecast of the medical personnel productivity. The authors use general scientific methods of analysis and synthesis, logical analysis; for data analysis standard methods of descriptive statistics were used. The forecast model is compiled by time series analysis using a cross-platform software package for econometric analysis Gretl. Materials for analysis included domestic and foreign literature, regulatory documentation for 2011–2021, as well as data of the Federal State Statistics Service. The authors present the experience of evaluating the medical personnel productivity of the Kemerovo Region – Kuzbass, reveal negative dynamics of the indicator, and make a forecast of its development. The article demonstrates various views of scientists and researchers on the problem of quantitative analysis of social workers performance and actualizes the problem of further analysis of the medical personnel labor productivity based on the methodology of multivariate analysis.